Effect of water content on thermal oxidation of oleic acid investigated by combination of EPR spectroscopy and SPME-GC-MS/MS. (15th April 2017) - Chen, Hongjian; Cao, Peirang; Li, Bo; Sun, Dewei; Wang, Yong; Li, Jinwei; Liu, Yuanfa
Highlights: The apply of EPR with DMPO as spin trap in thermal oxidation of oleic acid. Identification of alkyl spin adducts as the most abundant radical species. Higher percentage of (E, E)-2, 4- decadienal with higher water content. Abstract: Promotion of water to the thermal oxidation of oleic acid was detected by the combination of EPR, SPME-GC-MS/MS and GC. Spin-trapping technique was used to identify and quantify the radical species formed during thermal oxidation of oleic acid by using DMPO as electron spin trap. The most abundant radical species were identified as DMPO-alkyl radical adducts. EPR intensity plateau of the samples with 5% water content was 140% higher than the samples without water. It implies oleic acid samples with high water content had high level of oxidation rates. The proportion of aldehydes of the samples with 2% water content was the maximum about 59.97%. Among the formed products, (E, E)-2, 4-decadienal has genotoxic and cytotoxic effects, whose percentage was nearly twice comparing with that of 5–0% water content. This study demonstrated that higher water content in frying systems would contribute to seriously oxidation and degradation of oleic acids.